2019
DOI: 10.1002/joc.6255
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach for modelling pattern and spatial dependence structures between climate variables by combining mixture models with copula models

Abstract: Spatiotemporal dependence structures play a pivotal role in understanding the meteorological characteristics of a basin or subbasin. This further affects the hydrological conditions and, consequently, will provide misleading results if these structures are not taken into account properly. In this study, we modelled the spatial dependence structure of three climate variables, maximum and minimum temperature and precipitation, throughout the Monsoon‐dominated zone of Pakistan. For temperature, six meteorological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…When we examine the January 2017 minimum temperature prediction maps obtained by both methods, we see that copula prediction maps have more detail over the area and gave better results in extrapolation. The obtained results are in accordance with those of Alidoost et al (2018), Khan et al (2019), andDzupire et al (2020). Alidoost et al (2018) showed that spatial copulas with covariates outperform kriging predictions.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…When we examine the January 2017 minimum temperature prediction maps obtained by both methods, we see that copula prediction maps have more detail over the area and gave better results in extrapolation. The obtained results are in accordance with those of Alidoost et al (2018), Khan et al (2019), andDzupire et al (2020). Alidoost et al (2018) showed that spatial copulas with covariates outperform kriging predictions.…”
Section: Discussionsupporting
confidence: 85%
“…Alidoost et al (2018) showed that spatial copulas with covariates outperform kriging predictions. Khan et al (2019) showed that using C-Vine, D-Vine, and t-copula models resulted into accurate predictions of daily maximum and minimum temperature and precipitation. They found that copulas were good at capturing the spatial dependence structure between climatic variables.…”
Section: Discussionmentioning
confidence: 99%
“…It can efficiently be used in case of high correlation and even if different probability distributions for the variables exist to jointly simulate the drought variables (Salvadori and De Michele, 2010). Hence copula modelling has an advantage over traditional multivariate distributions that it can be used for similar as well as different probability distributions of the variables and existing high correlation in several fields (e.g., Shiau, 2006; Lee and Cook, 2019; Yu et al ., 2020; Bazrafshan et al ., 2020; Khan et al ., 2020; Deng and Liang, 2021; Ullah and Akbar, 2021a; 2021b). In literature, copula models have also been effectively used in the development of new multivariate indices or in combing the results of existing indices (e.g., Kavianpour et al ., 2018; Van de Vyver and Van den Bergh, 2018; Wang et al ., 2020; Won et al ., 2020; Amjad et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…They (Khan et al. 2020 ) apply regular (C- and D-) Vine copula and the Student t-copula to explore the structure of spatial dependence of different climate variables, for instance, precipitation, and air temperature. A combination of extreme value models like the Generalized Pareto Distribution (GPD) with copulas (Masseran and Hussain 2020 ) illustrate a dependence between and a set of four major pollutant variables, namely, CO, NO , SO , and O .…”
Section: Introductionmentioning
confidence: 99%